Effect of fish length and nutritional condition on the fecundity of distressed Atlantic cod Gadus morhua from the Baltic Sea. Issue 4 (26th February 2018) - Mion, M.; Thorsen, A.; Vitale, F.; Dierking, J.; Herrmann, J. P.; Huwer, B.; von Dewitz, B.; Casini, M.
Abstract : The disappearance of larger individuals and the decrease in individual body condition suffered by Atlantic cod Gadus morhua in the eastern Baltic during the past two decades can be expected to affect the stock reproductive output. To investigate this, female G. morhua were collected during the spawning and pre‐spawning period in 2015−2016. The current individual potential fecundity ( F P ) of eastern Baltic G. morhua was estimated and analysed in relation to total length ( L T ) and indices of nutritional status such as body condition ( K ) and hepato‐somatic index ( I H ) using generalized linear models. In addition, the current prevalence of atresia and its potential relation to K were investigated. Moreover, a calibration curve to estimate F P from oocyte diameter, based on the autodiametric oocyte counting method, was established for the first time for eastern Baltic G. morhua and can be used for future fecundity studies on this stock. The results showed that F P was mainly positively related to fish length, but K and I H also contributed significantly to the variation in F P . The model predicted that fish with K  = 1·2 have a F P 51% higher than fish of the same L T with K  = 0·8. The prevalence of fecundity regulation by atresia was 5·8%, but it was found only in fish in the pre‐spawning maturity stage and with low K . Temporal changes in biological features such as the length composition and individual body condition of eastern Baltic G. morhua, should be accounted for when estimating stock reproductive potential.